Three Essays in Development Economics: First Nation Economic Development - Rice, Derek (Université d'Ottawa / University of Ottawa, 2018)
This dissertation contains three essays in the economics of development. The first essay investigates the effects of the decentralization of governance over education to communities in terms of individual education outcomes. The next essay relates to the first by exploring the factors that drive communities to adopt decentralized governance, including forms of decentralized governance over education. The last essay returns to the topic of education by examining a policy aimed at decreasing the costs of post-secondary education for a minority group. Each essay probes these topics within the context of First Nations in Canada. The first essay examines the substantial impacts of education decentralization on high school attendance and completion through the analysis of First Nation education self-government agreements in Canada. These agreements are important institutional arrangements that transfer the authority over education from the federal government to First Nations. I exploit confidential microdata and exogenous variation in the implementation of education self-government agreements to perform the analysis. My results indicate that self-government agreements focused exclusively on education increase high school attendance by 5 to 9 percentage points and high school completion by 3 to 5 percentage points. However, the effects on high school completion rates under multi-sectoral self-government agreements implemented together with comprehensive land claim agreements and for self-government agreements that focus on education alone differ dramatically for women and men. High school completion improves by 8 to 11 percentage points for women, but drops by a staggering 17 to 25 percentage points for men. These results have important policy implications for education decentralization in general, along with implications for the particular case of First Nation education self-governance in Canada. The second essay identifies the determinants of decentralized governance by exploring the First Nation self-government agreement claim and implementation processes. I use a novel dataset on self-government agreements and confidential microdata to perform the analysis. My results support the notion that we can treat self-government treatment variables as exogenous, when controlling for reserve fixed effects. This is not an onerous condition to impose. Specifically, I do not find any factors of economic or statistical significance for claims for my richest and most-preferred specification, which includes controlling for reserve fixed effects. Contrary to the results for claims, I find that education and income are important factors for implementation, but only conditional on a reserve having previously made a claim. However, this significance disappears, once I relax this condition and compare the determinants of implementation against reserves that may or may not have made a claim. The third essay examines the substantial impacts of a targeted policy that provides postsecondary tuition and living expense subsidies for Aboriginal Canadians. To identify the effects of the policy, I exploit a reform of the policy's eligibility requirements in 1985 that lead to a large increase in the number of individuals with access to the subsidies. My results indicate that the reform lead to economically and statistically significant increases in the likelihood of attaining any post-secondary education for a group of women whose eligibility was particularly targeted by the reform and for women generally. These increases range from about 4 to 7 percentage points. The effects for men are positive, but much smaller and not significant.